PELATIHAN PENYUSUNAN PITCHING DECK BISNIS DAN KEUANGAN UNTUK WIRAUSAHA MAHASISWA UNIVERSITAS RIAU - Julita, Julita; wahyuni, Nita; Nasrizal, Nasrizal; Iznillah, Muhammad Luthfi (Jurnal Abdi Insani, 2024)
Micro, Small and Medium Enterprises (MSMEs) are one of the drivers of the economy in Indonesia. To be able to continue to grow and develop sustainably, various ways are needed to improve the competence of business actors. One of them is through training in the preparation of business and financial pitching decks for Riau University student entrepreneurs. This service activity aims to provide education and training on the preparation of business and financial pitching decks and business presentation training for Riau University student entrepreneurs. The method of implementing this activity is by providing lectures and workshops related to the material, namely business and financial pitching decks. This activity was carried out for student entrepreneurs who are members of the campus entrepreneur community, namely the Riau University Entrepreneur Community (UNRIES) on September 16, 2023. With a total of 59 participants. As a result of this training, it is hoped that the business started by the students can continue to be sustainable Pitching decks have an important role in helping to develop the business of MSME players, including student MSMEs. The ability to create a business and supported by the ability to present its business potential will open access to capital. This access is needed to find business partners in the form of capital cooperation. The ability of student entrepreneurs to open access to capital will accelerate their business growth.